2018
DOI: 10.1515/jpem-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness as a measure of cardiovascular risk in obese adolescents and adolescents with diabetes type 1

Abstract: Background Cardiovascular disease (CVD) is the end result of vascular aging and atherosclerosis, having its origins in childhood. The aim of our study was to compare arterial stiffness (AS) and intima-media thickness (IMT) as markers of an early vascular damage between obese adolescents, adolescents with diabetes type 1 (T1D) and lean control subjects. Methods We analyzed AS and IMT in 68 obese adolescents (13.27±2.31 years), 42 adolescents with T1D (14.95±2.35 years) lasting over 5 years and 38 controls (15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…[7] Conflicting results were reported in a European study, which found no significant correlations between arterial stiffness, gender, age, BMI, Tanner stage or SBP levels among 38 non-obese adolescents (mean age and associated standard deviation (SD): 15.02 (1.94) years). [8] The same study reported a significant association between arterial stiffness and SBP among 68 obese adolescents (mean (SD) age: 13.27 (2.31) years). [8] This could imply that early vascular damage is more apparent in obese adolescents than in their lean counterparts.A greater understanding of arterial stiffness and its association with conventional CVD risk factors is warranted.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…[7] Conflicting results were reported in a European study, which found no significant correlations between arterial stiffness, gender, age, BMI, Tanner stage or SBP levels among 38 non-obese adolescents (mean age and associated standard deviation (SD): 15.02 (1.94) years). [8] The same study reported a significant association between arterial stiffness and SBP among 68 obese adolescents (mean (SD) age: 13.27 (2.31) years). [8] This could imply that early vascular damage is more apparent in obese adolescents than in their lean counterparts.A greater understanding of arterial stiffness and its association with conventional CVD risk factors is warranted.…”
mentioning
confidence: 87%
“…[8] The same study reported a significant association between arterial stiffness and SBP among 68 obese adolescents (mean (SD) age: 13.27 (2.31) years). [8] This could imply that early vascular damage is more apparent in obese adolescents than in their lean counterparts.A greater understanding of arterial stiffness and its association with conventional CVD risk factors is warranted. Furthermore, it has been reported that black South African (SA) children are at an increased risk of developing CVD.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Excess caloric intake prompts the onset and development of vascular stiffness to compromise vascular function via endothelial dysfunction, extracellular matrix remodeling, calcification, and inflammation ( 202 204 ). Arterial stiffness is usually monitored clinically using pulse wave velocity ( 205 , 206 ). Weight gain and metabolic disorders occur before, or concomitant with, arterial stiffening ( 189 , 207 212 ).…”
Section: Cardiac Remodeling In Obesitymentioning
confidence: 99%
“…1), but they did not belong to the subgroup with bad metabolic control (HbA1c 7.3 and 7.8, respectively, data not shown in the study). Furthermore, not all studies described an increase in carotid IMT in adolescents with T1D [1,2].…”
mentioning
confidence: 94%